Cadmium accumulation and antioxidative defences in Brassica juncea L. Czern, Nicotiana tabacum L. and Solanum nigrum L. - Pinto, Ana P. (2012)
Remediation of sites contaminated with heavy metals using hyperaccumulators seems a promising alternative to engineering approaches. In this work, we compared cadmium (Cd) accumulation and tolerance (based on responses to oxidative stress) in three different species, Brassica juncea (L.) Czern, Nicotiana tabacum L. and Solanum nigrum L., described in the literature as very tolerant or even as hyperaccumulators. The plants were grown in soil spiked with different Cd concentrations (0 – 35 mg kg−1) over a period of 90 days. The translocation factor (TF), used to measure the effectiveness to translocate Cd from roots to shoots, depended greatly on the species. N. tabacum was the plant which exhibited the highest TF values. It was the only plant under study that fulfilled the conditions of a hyperaccumulator for all levels of soil contamination. On the other hand, S. nigrum presented the highest Cd concentration in plant tissues, with TF >1 in the presence of 5 mg Cd kg−1 of soil. Although B. juncea had presented the lowest TF and Cd concentrations, it was the only plant with TF values increasing with the level of cadmium. Oxidative stress in plants was evaluated by lipid peroxidation and activities of catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPX) and superoxide dismutase (SOD), both in roots and shoots. A significant enhancement (versus control) on lipid peroxidation and enzymatic activity of CAT and APX in shoots of B. juncea, N. tabacum and S. nigrum was observed for the highest levels of Cd in soil, 15 and/or 35 mg Cd kg−1. B. juncea presented the most sensitive response of GPX, for all levels of Cd in soil. Lipid peroxidation and CAT activity were greater in shoots than in roots for all plants and soil Cd concentrations. SOD activity did not present consistent trends for any plant.